Sistem Pendukung Keputusan Pemilihan Ekstrakulikuler Sekolah Terbaik dengan Menggunakan Metode Multi Attribute Ultility Theory (MAUT) - Masitoh, Agustine Hana (Journal of Information System Research (JOSH), 2025)
The development of technology that is currently developing very rapidly is very helpful in learning activities at school. Technology has a very important role in education. Education is one of the potentials that is needed to improve activities in schools. These activities are extracurricular activities. Extracurricular or extracurricular activities are activities to develop the talents of students who are outside the classroom or outside class hours and are not required by students to carry out these activities. school as the goal of increasing knowledge, skills, and insight as well as shaping the character of students according to their respective interests and talents. This study aims to build a decision support system (DSS). Where has a function in determining decision making in the process of determining the best school extracurricular activities by establishing the MAUT method. And get the results of the first rank correctly and the first alternative is A2 with a preference value of 0.806 which is found in volleyball exuls.